If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 62x + 19 + -3x = 15 + -1(3x + 7) Reorder the terms: 19 + 62x + -3x = 15 + -1(3x + 7) Combine like terms: 62x + -3x = 59x 19 + 59x = 15 + -1(3x + 7) Reorder the terms: 19 + 59x = 15 + -1(7 + 3x) 19 + 59x = 15 + (7 * -1 + 3x * -1) 19 + 59x = 15 + (-7 + -3x) Combine like terms: 15 + -7 = 8 19 + 59x = 8 + -3x Solving 19 + 59x = 8 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 19 + 59x + 3x = 8 + -3x + 3x Combine like terms: 59x + 3x = 62x 19 + 62x = 8 + -3x + 3x Combine like terms: -3x + 3x = 0 19 + 62x = 8 + 0 19 + 62x = 8 Add '-19' to each side of the equation. 19 + -19 + 62x = 8 + -19 Combine like terms: 19 + -19 = 0 0 + 62x = 8 + -19 62x = 8 + -19 Combine like terms: 8 + -19 = -11 62x = -11 Divide each side by '62'. x = -0.1774193548 Simplifying x = -0.1774193548
| 14=k/7 | | 1/5(750+200) | | -5n=250 | | 7z+11=2z-8 | | 7x-12=2x+12 | | 6x+8x-36=3x | | 6n-3(4-n)=-30 | | 8(4-3p)=4(3-5p)+4p | | 4x-6=-6-4 | | 0=20x^2+10x | | 1.5x-1=3.5 | | 0=20x^2+10 | | 1/2(y+7)=17 | | -4x-11x=75 | | 1.5x-1=-4 | | 307=2x-57 | | x^2-13x-90=8 | | 3x-11x=-48 | | 3/4=x/500 | | -2(x-3)=-2x+6 | | 7-2[-6-(2-5)]= | | 4x+8y=-32 | | .33(10x-5)=3 | | 1/2y+12=6 | | 15x+7=-23 | | 5e+2=2e-2 | | g(x)=-log(x) | | 12x=5/6 | | 12x+5/6 | | 12v^2=-10v-10 | | -9(z+3)-5(2z+10)= | | 8x+4-2x=-5+4x |